The silent struggle: screening for attention-deficit/hyperactivity disorder symptoms and academic performance among undergraduate medical students - Vijay Kumar; Vandana Kain; Sanjeev Kumar (International Journal Of Community Medicine And Public Health, 2026)
Background: Attention-deficit/hyperactivity disorder (ADHD) frequently persists into adulthood and can adversely affect academic performance. Medical students are particularly vulnerable due to the demanding nature of medical education. This study estimated the prevalence of ADHD symptoms and examined their association with academic performance among undergraduate medical students. Methods: A cross-sectional study was conducted among 214 undergraduate MBBS students at LLRM Medical College, Meerut. Participants were selected by convenient sampling. ADHD symptoms were assessed using the adult ADHD self-report scale (ASRS-v1.1). Students with ≥4 positive responses in Part A were classified as ADHD screen-positive. Data were analyzed using Jamovi software, applying Chi-square or Fisher’s exact test. Results: Of the 214 participants, 31 (14.4%) screened positive for ADHD symptoms. ADHD positivity was significantly associated with lower examination scores (p=0.033), history of failure in professional examinations (p=0.0062), and poor self-rated academic performance (p